Asymmetric and threshold price transmission dynamics in onion markets in India - James Kofi Blay; Akshata Nayak; Isaac Abunyuwah; Huchaiah Lokesha; Gracy Chennothumalil Paily (Cogent Economics & Finance, 2024)
Functional agricultural marketing system is purported to be the silver bullet and multiplier for stimulating production and consumption and, accelerating the pace of economic and rural enterprise development. Thus, understanding effectiveness of agricultural products market price transmission dynamics in a functional agricultural marketing system is useful for all sections of societies concerned with the marketing of agricultural produce. Thus, this study was conducted to assess the market middlemen response to onion price perturbation. To stimulate policy evaluation and intervention in India onion markets, seven majors' onion markets namely: Lasalgaon (reference market), Kanpur, Mumbai, Lucknow, Korzhikode, Mysore, and Hyderabad were examined using monthly wholesale prices from January 2011 to December 2018. Market middlemen response to price shocks was examined through the framework of momentum threshold autoregressive model and a regime-switch asymmetric threshold vector error correction model. The results of the estimation procedure revealed that the markets were characterized by threshold co-integration and asymmetric response adjustment path both in the short and long run. The study results indicated that wholesalers responded faster to deviations that tend to increase their profit margin but delayed in responding to prices changes that tend to benefit the producers. We recommend stringent measures against intensification of existing regulated marketing structures that seek to favour middlemen at the expense of producers and consumers and, the conscious effort to improve market intelligence structure for efficient conduct and performance of onion markets in India. The results of the estimation procedure revealed that the markets were characterized by threshold co-integration and asymmetric response adjustment path both in the short and long run. The study results indicated that wholesalers responded faster to deviations that tend to increase their profit margin but delayed in responding to price changes that tend to benefit the producers.
Keywords: 330; asymmetric; market dynamics; Prices; threshold model